Screening of antimicrobial activity of citrus essential oils against pathogenic bacteria and Candida strains. (18th February 2019) - Mancuso, Monique; Catalfamo, Maurizio; Laganà, Pasqualina; Rappazzo, Alessandro Ciro; Raymo, Vilfredo; Zampino, Daniela; Zaccone, Renata
Abstract: Several studies have indicated that plants are good sources of antimicrobial agents and pharmaceuticals. The present study is focused to evaluate the antimicrobial potential of 11 citrus essential oils (EOs) and terpenes (T), against 18 bacterial pathogenic strains and 4 Candida sp. strains. Volatile compounds present in the citrus EOs were determined by a gas chromatography analysis, allowing the identification of 79 components. Results highlights that lemon, bergamot oil and terpene were effective against more than 54.5% of tested bacteria. Candida spp. strains resulted very sensitive to all terpenes and EOs. Gram negative bacteria showed lower sensitivity than Gram positive ones. Among Gram negative, fish pathogens were sensitive to oils, so we suggested their use as possible alternatives in aquaculture farms to prevent bacterial fish diseases. Moreover, results suggested that citrus oils could be a useful tool in the food industry to prolong the shelf‐life. Abstract : The antimicrobial activity of 11 Citrus essential oils were tested against 18 bacterial pathogenic strains and 4 Candida sp. strains highlighting the effectiveness of lemon, bergamot oil and its terpene.